Potential Economic Benefit and Producers’ Willingness to Adopt Bt-Brinjal in Bangladesh: An Ex-Ante Analysis - Al Mamun, Md. Abdullah; Alam, Mohammad Jahangir; Ethen, Dilshad Zahan; Barua, Swarup (International Journal of Sustainable Agricultural Research, 2019)
Introduction of genetic engineering in agriculture is a recent idea of native scientists. Scientists from Bangladesh Agriculture Research Institute (BARI) are working on developing an FSB resistant brinjal variety namely Bt-brinjal in collaboration with Cornel University, USA. In addition, this study was attempted to find out the potential economic benefit and producers’ willingness to adopt Bt-brinjal. A total of 80 respondents were randomly selected from Gazipur and Jamalpur districts. Descriptive statistics and Logistic regression analysis were used to analyze data. Yield gain and reduction in insecticide use data give the result as Bt-brinjal will increase yield by 65.76 percent and 44.87 percent and reduce pesticide cost by 71 percent and 70.36 percent compared to local OPV and Hybrid brinjal respectively. 98 percent of farmers will produce Bt-brinjal if they reduce insecticide use but 65 percent will not produce it if there are any health-related issues. Mass advertisement is also a significant factor of adoption (63.75 percent). It was found that the marketing channel for Bt and non-Bt brinjal is same. For this producers’ adoption of Bt-brinjal is related to the potential benefit and harmlessness of the technology. Results also showed that adoption is significantly influenced by education, own land size, no. of spray per season, season of growing brinjal (p<.01) and household size, type of growing brinjal (p<.05) respectively. Though voice against GM crops was also very loud but the Bangladesh government is very much eager to introduce this technology to the market and give the benefits to its consumers.